Analysis of Hexagonal Head Bolt Production of M10 × 100 mm at a Capacity of 500 Units/Hour - Muhammad Afaq Ahmad Khan; Syamsul Hadi; Ramadhani Rafi Rasheesa; Sulaiman Sulaiman (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
The problem lies in the inconsistent quality of M10 hexagonal head bolts with a spacing of 1.5 mm, a bolt length of 100 mm and slow production speed for manual production. The purpose of the analysis is to obtain consistent, standard, and productive quality of M10 hexagonal head bolts with a spacing of 1.5 mm, a bolt length of 100 mm. The analysis method includes the selection of AISI 1040 raw materials with a diameter of 10 mm in the form of rolls, the determination of the production process through raw material inspection, diameter reduction from 10 mm to 9.8 mm, the formation of hexagonal heads with a machine, cutting the length of the bolts and the bolt end chamfer, making M10 threads with a range of 1.5 mm with a machine, hardening, 10 m thick Zinc coating, thread profile inspection, sample hardness test, and sample tensile test. The results of mass production with the machine obtained a hexagonal head bolt with a thread size of M10x1.5 mm, a bolt length of 100 mm, a capacity of 500 units/hour in accordance with the ISO 9001:2015 standard with a hardness of 30 HRC and a tensile strength of 830 MPa at a cost of Rp. 1133/bolt and a process duration of 8.3 minutes/bolt which implies that product quality can be more guaranteed to be consistent and uniform.